In-vivo study of morphology of embryo in the medicinal plant, Basella alba Linn. (Basellaceae) - Labhane NM; Dongarwar NM; Borkar SJ (International Journal of Life Sciences, 2014)
The present paper deals with morphology of freshly dissected out live embryos of medicinally important plant, Basella alba Linn. The various part of the plant is used to cure dysentery, diarrhea, anemia, cancer etc. It is also has a known antioxidant, anti mutagenic, infertility, central nervous system depressant and anti inflammatory activity. The study of embryo at maturity in its native form is very significant, since its normal development is related to the viability of the seed. The young and mature embryo can be distinguished with the help of presence of chlorophyll. The viability of seeds is determined by the presence of green embryo at maturity, while nonviable seeds contains white coloured embryo. The embryo is coiled twice at young stage, while at maturity it is coiled one and half times, with the growing tip situated at the centre and the radicle on the outer side. Considering the medicinal value of B. alba, study the reproductive biology with respect to structure of mature embryo is very pertinent. The study of embryo in its native form also shows the manner in which the growing tip is protected by coiling so as to ensure that the species is protected against adverse condition.